Acinar cell carcinoma with PRKAR1A and PTEN alterations and paraneoplastic panniculitis. Issue 12 (22nd December 2022) - Yang, Zhizhou; Zarate Rodriguez, Jorge G; Beck, Haley; Byrnes, Kathleen; Trikalinos, Nikolaos A; Hammill, Chet W
Abstract : Pancreatic acinar cell carcinoma is a rare type of pancreatic malignancy, which can be confused with pancreatic neuroendocrine neoplasm. Here, we describe a woman in her 80s who presented with abdominal pain and bilateral lower extremity panniculitis. She underwent surgery for a presumed diagnosis of neuroendocrine tumour with PTEN and PRKAR1A alterations; 19 months, later, a recurrence of her pancreatic malignancy was discovered. The patient underwent repeat resection and this time immunohistochemical staining confirmed the diagnosis of acinar cell carcinoma. Staining for acinar cell carcinoma should be prompted based on clinical suspicion in context of PTEN or PRKAR1A mutation when appropriate.